PENERAPAN MANAJEMEN PAUD DALAM PROGRAM PARENTING UNTUK MENUNJANG TUMBUH KEMBANG ANAK DIDIK USIA DINI DI POS PAUD AL MAKMUN DESA GULBUNG KECAMATAN - Juwairiyah; Maimina (CV. Jendela Gagasan, 2024)
This study aims to describe: (1) How is the implementation of PAUD management in parenting programs to support the growth and development of early childhood students at the Al Makmun PAUD Post (2) What are the supporting and inhibiting factors for the implementation of PAUD management in parenting programs to support the growth and development of early childhood students at the Al Makmun PAUD Post. In its implementation, the parenting program at the Al Makmun PAUD Post is divided into 4 stages. First, Parents gathering, a meeting between parents and the PAUD institution to discuss PAUD institution programs in relation to child guidance and care. Second, the seminar activities carried out in the framework of the parenting program by inviting competent PAUD experts or practitioners, a storyteller, a child psychologist, village midwife, BKB and health center. Third, Home Education Video A series of activities at school and sending children's learning activities from PAUD institutions to parents in the form of videos and sent via the Al Makmun PAUD Post group WhatsApp media, so that parents can watch at home as well as parents who are at home send a series of videos of children's activities at home when children play or study accompanied by parents and the videos are sent to the PAUD group. Fourth, Evaluation to improve the implementation of the parenting program in order to achieve maximum growth and development of early childhood students, activities carried out by the Al Makmun PAUD Post using the Deliberation method.